The Spirit throughout the Canon : Pentecostal Pneumatology - Oliverio, L. William,; Keener, Craig S., (Journal of Pentecostal Theology Supplement Series ;, 2022)
Pentecostal forms of Christianity have now taken a dynamic role in contemporary Christianity, often at the vanguard of new movements and spiritual vitality among Christians in the late modern world. The many movements which constitute global Pentecostalism share in common an intense commitment to the Bible and life in the Spirit. Over the past several decades, Pentecostal biblical scholarship has played an important role in resourcing Pentecostal theologies. These elements come together in this volume in which leading Pentecostal biblical scholars from around the world account for the appearance of the divine Spirit, putting forth a defining work from a seminal generation of scholars. Contributors are: J. Ayodeji Adewuya, Kenneth J. Archer, Melissa Archer, Emma M. Austin, Holly Beers, Michael L. Brown, Blaine Charette, Jacob Cherian, Roger D. Cotton, Daniel K. Darko, Finny Philip, Roji Thomas George, Jacqueline Grey, Alicia R. Jackson, Wonsuk Ma, Lee Roy Martin, Robert P. Menzies, Brian Neil Peterson, Rebecca Skaggs, Joe Thomas, John Christopher Thomas, Robby Waddell, Rick Wadholm, Nimi Wariboko, Cynthia Long Westfall.